2021
DOI: 10.1021/acs.jpca.0c08731
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Formation of C5H6 Isomers via the Crossed Molecular Beam Reaction of the Methylidyne Radical (CH; X2Π) with 1,2-Butadiene (CH3CHCCH2; X1A′)

Abstract: The bimolecular gas-phase reaction of the methylidyne radical (CH; X 2 Π) with 1,2-butadiene (CH 2 CCHCH 3 ; X 1 A′) was investigated at a collision energy of 20.6 kJ mol −1 under single collision conditions. Combining our laboratory data with high-level electronic structure calculations, we reveal that this bimolecular reaction proceeds through the barrierless addition of the methylidyne radical to the carbon−carbon double bonds of 1,2-butadiene leading to doublet C 5 H 7 intermediates. These collision adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The initial interaction between the reactants may occur via methylidyne addition to acetylenic carbon atoms or to the triple CC bond of 1-butyne and methylidyne insertion into various C–H bonds of the C 4 H 6 molecule. The doublet C 5 H 7 PES was investigated gradually and systematically, in continuation of our previous CH + 1,3-/1,2-butadiene studies , and keeping the notation of intermediates and bimolecular products consistent with the previous works. Here, our calculations showed that the methylidyne radical plus 1-butyne system accesses 21 C 5 H 7 intermediates ( i98–i117 and complex2 ) and 92 transition states, leading to the hydrogen atom emission C 5 H 6 products ( p1 , p4 , p7 , p9 , p10 , p15 , p16 , p20 , p30 , p36 , p45 , p46 , and p50 ), methyl radical elimination C 4 H 4 products ( p23 , p32 , p35 , and p51 ), ethyl radical loss C 3 H 2 products ( p43 , p44 , and p47 ), linear C 3 H radical emission C 2 H 6 product ( p48 ), propargyl radical loss C 2 H 4 product ( p24 ), and allyl CH 2 CHCH 2 and 3-propenyl CH 3 CHCH radical loss C 2 H 2 products ( p37 and p49 , respectively) (Figures , , , , ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial interaction between the reactants may occur via methylidyne addition to acetylenic carbon atoms or to the triple CC bond of 1-butyne and methylidyne insertion into various C–H bonds of the C 4 H 6 molecule. The doublet C 5 H 7 PES was investigated gradually and systematically, in continuation of our previous CH + 1,3-/1,2-butadiene studies , and keeping the notation of intermediates and bimolecular products consistent with the previous works. Here, our calculations showed that the methylidyne radical plus 1-butyne system accesses 21 C 5 H 7 intermediates ( i98–i117 and complex2 ) and 92 transition states, leading to the hydrogen atom emission C 5 H 6 products ( p1 , p4 , p7 , p9 , p10 , p15 , p16 , p20 , p30 , p36 , p45 , p46 , and p50 ), methyl radical elimination C 4 H 4 products ( p23 , p32 , p35 , and p51 ), ethyl radical loss C 3 H 2 products ( p43 , p44 , and p47 ), linear C 3 H radical emission C 2 H 6 product ( p48 ), propargyl radical loss C 2 H 4 product ( p24 ), and allyl CH 2 CHCH 2 and 3-propenyl CH 3 CHCH radical loss C 2 H 2 products ( p37 and p49 , respectively) (Figures , , , , ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, our calculations showed that the methylidyne radical plus 1-butyne system accesses 21 C 5 H 7 intermediates ( i98–i117 and complex2 ) and 92 transition states, leading to the hydrogen atom emission C 5 H 6 products ( p1 , p4 , p7 , p9 , p10 , p15 , p16 , p20 , p30 , p36 , p45 , p46 , and p50 ), methyl radical elimination C 4 H 4 products ( p23 , p32 , p35 , and p51 ), ethyl radical loss C 3 H 2 products ( p43 , p44 , and p47 ), linear C 3 H radical emission C 2 H 6 product ( p48 ), propargyl radical loss C 2 H 4 product ( p24 ), and allyl CH 2 CHCH 2 and 3-propenyl CH 3 CHCH radical loss C 2 H 2 products ( p37 and p49 , respectively) (Figures , , , , ; Table ). Because some pathways of the CH + 1-butyne reaction eventually access the intermediates considered earlier, in the studies of CH reactions with the other C 4 H 6 isomers, , we occasionally stop the PES presentation and our discussion at the common intermediates. Moreover, as will be seen ( vide infra ) from the calculations of product branching ratios, the prevalent reaction products would be formed through relatively short pathways, which do not involve the common intermediates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations